Cabo Delgado in Peace: Memories and Forebodings - Santimano, Sérgio; Israel, Paolo (Kronos, 2024)
In 1996, Mozambican photographer Sérgio Santimano travelled to Cabo Delgado to carry out photographic work, with the objective of documenting the province in a time of peace and renewal. His travels resulted in the exhibition, Cabo Delgado: A Photographic Story about Africa (Cabo Delgado: uma história fotográfica sobre África), which consolidated his international renown. In this photo-essay, we revisit a selection of Santimano's photographs on Cabo Delgado, with the aim of offering an image different from that of devastation and death which has dominated the national and global news since an Islamist insurgency erupted in the province in October 2017. While providing a pathway into memories of Cabo Delgado as a place rich with life, history, culture and individuality, Santimano's photographs also offer eerie forebodings of the present.